2017
DOI: 10.5005/jp-journals-10032-1100
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Risk Factors for Surgical Site Infection in Gynecologic Oncology Surgeries at a Tertiary Care Facility in a Developing Country

Abstract: Introduction: Surgical site infections (SSIs) are among the most common complications in surgical patients and have serious consequences for outcomes and costs. There is a dearth of information on risk factors for developing SSI in patients undergoing gynecologic cancer surgery, and this has not been studied using national data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…The dirty and contaminated wound found on follow-up might be due to substandard care at home. According to the results SSI rates were higher in gastrointestinal surgeries, which is similar to a study conducted at the Khyber Teaching Hospital, Peshawar by Khan et al who also reported high prevalence rate of SSI with gastrointestinal surgeries (13.51%) 16.…”
supporting
confidence: 87%
“…The dirty and contaminated wound found on follow-up might be due to substandard care at home. According to the results SSI rates were higher in gastrointestinal surgeries, which is similar to a study conducted at the Khyber Teaching Hospital, Peshawar by Khan et al who also reported high prevalence rate of SSI with gastrointestinal surgeries (13.51%) 16.…”
supporting
confidence: 87%
“…Of these, 195 unique articles were selected by title or abstract data; 98/195 of these did not meet the inclusion criteria. This left a total of 99 articles for evaluation: 34 from Asia (Austin et al, 2004;Duerink et al, 2006;Kanafani et al, 2006;Wu et al, 2006;Ali et al, 2009;Buang and Haspani, 2012;Ee et al, 2014;El Beltagy et al, 2010;Khan et al, 2010Khan et al, , 2011Lee et al, 2007Lee et al, , 2010Lee et al, , 2015Malik et al, 2009;Mathur et al, 2013;Memon et al, 2013;Nausheen et al, 2013;Sangrasi et al, 2008;Saramma et al, 2011;Akhter et al, 2016;Al-Mulhim et al, 2014;Bibi et al, 2015;Hey et al, 2017;Jyothirmayi et al, 2017;Mehrabi Bahar et al, 2015;Mundhada and Tenpe, 2015;Ng et al, 2015;Pardhan et al, 2013;Sahu et al, 2016;Shah et al, 2015Shah et al, , 2017Singh et al, 2015;Vaze et al, 2014;Yu et al, 2015), 27 from LATAM (Alvarez-Moreno et al, 2014;Bannura et al, 2016;Barbosa et al, 2004;Bellusse et al, 2015;da Cunha et al, 2011;…”
Section: Resultsmentioning
confidence: 99%
“…,Gao et al (2010),Gil-Londoño et al (2016),Giri et al (2008),Hafez et al (2012),Hao et al (2013),Hernaiz-Leonardo et al (2017),Hey et al (2017),Ibrahim et al (2014),Jyothirmayi et al (2017),Kanafani et al (2006),Khan et al (2010),Khan et al (2011),Ledur et al (2011),Lee et al (2007),Lee et al (2010),Lee et al (2015),Legesse Laloto et al (2017),Leon et al (2011),Li et al (2013),Liu et al (2017),Lyimo et al (2013),Madu et al (2011), El Maerrawi and Carvalho (2015),Malik et al (2009),Martins et al (2008),Marwa et al (2015),Mathur et al (2013),Mawalla et al (2011),Mehrabi Bahar et al (2015),Memon et al (2013),Mundhada and Tenpe (2015),Nagaya et al (2017),Ng et al (2015),Ning et al (2014),Nwankwo and Edino (2014),Oliveira and Carvalho (2004),Pardhan et al (2013), Porras-Hernandez et al (2008,Portillo-Gallo et al (2014),Qi et al (2013),Qin et al (2014),Qiu et al (2011),Rabiu ...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Considering the lack of evidence that prolonged antibiotic prophylaxis prevents SSI and the possible associated side effects of antibiotics, the WHO expert panel unanimously agreed that antibiotic prophylaxis should not be continued in the presence of a wound drain. Similarly regarding the removal of drain, very low quality evidence shows that the early removal of wound drains has neither benefit nor harm in reducing the SSI rate when compared to late removal of drains (at postoperative day 6 or 4 later). Results were also similar when comparing early removal with removal determined according to the volume of drainage.…”
Section: Discussionmentioning
confidence: 99%